Peircean Index in the Naming Process: Nouns, Pronouns and Proper Names - West, Donna (Public Journal of Semiotics, 2013)
This analysis identifies semiotic differences between pronouns, proper names and count and mass nouns. It showcases the work of Peirce’s Index in the process of individuation, capitalizing upon the ontological and epistemological effects of employing pronouns (particularly demonstratives) as individuals, as opposed to their use as singulars. Peirce’s individual versus singular distinction highlights the contrast between unique separateness, on the one hand, and similarity among entities (i.e., object classification) on the other. The argument is likewise made that while pronouns are often used as individuals, nouns and most proper names have a singular function. Rationale supports the fact that this difference results from the prominence of Peirce’s Dynamical Object in the work of embodied schemas which underlie and permeate new experiences. Dynamical Objects of demonstrative pronouns ground the triad, while Interpretants ground triads for nouns and proper names.